Budaya Mengikuti Tren Berbahaya di Era Digital:: Kylie Jenner Lip Challenge dan Hahu Hoheng - Naiva Aqila Lubis; Tanwiral Hayati; Naurah Kamila (Sadida Islamic Communications and Media Studies, 2026)
The rapid development of social media has accelerated the spread of digital trends that are followed by people from various age groups. Although some trends have positive impacts, many viral trends pose potential health risks, such as the Kylie Jenner Lip Challenge and the Hahu Hoheng Challenge, which involves consuming extremely hot food. This study aims to analyze the factors that encourage people to participate in dangerous social media trends and examine their impacts. The research employed a qualitative approach using library research, observation of two TikTok videos selected through purposive sampling, documentation, and data analysis consisting of data reduction, data display, and conclusion drawing. This study applies George Gerbner's Cultivation Theory to explain how repeated exposure to social media content can shape users' perceptions that dangerous trends are normal and acceptable to imitate. The findings indicate that both trends may have negative consequences, including health problems, increased imitative behavior among children and adolescents, and social pressure influenced by curiosity and Fear of Missing Out (FOMO). These findings suggest that the popularity of a trend is often prioritized over consideration of its potential risks. Therefore, strengthening digital literacy, critical thinking skills, and supervision of social media use is essential to encourage people to be more selective and responsible in responding to trends circulating in the digital environment.